1991
DOI: 10.1159/000173390
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation in Renal Function of the Obese Rat

Abstract: The influence of food and water intake on renal function was assessed by comparisons between the hyperphagic Zucker obese rat and its lean littermate, which demonstrates nocturnal dominance in activity. Serum creatinine and cortisol levels, creatine kinase activities, creatinine and urine clearances, and sodium and potassium excretion rates were measured over a 24-hour period in both lean and obese rats (n = 24 each). Six rats in each group were studied every 8 h to permit characterization over a 12-hour light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This model is particularly well adapted to chronophysiological investigations because it permits, without external surgical disturbance, the continuous determination of circadian changes in inulin and PAH clearance. Overall, it makes possible a better evaluation of 24-h variations in renal hemodynamics than does the method involving endogenous creatinine clearance as previously used in normal and obese rats (9,22). The present study documented circadian rhythmicity in GFR and RPF in chronically catheterized, unanesthetized, and freely moving rats, sampled repeatedly at 4-h intervals during the 24 h. Reproducible circadian changes were noted between animals and in the same animal assessed on consecutive days.…”
Section: Discussionsupporting
confidence: 60%
“…This model is particularly well adapted to chronophysiological investigations because it permits, without external surgical disturbance, the continuous determination of circadian changes in inulin and PAH clearance. Overall, it makes possible a better evaluation of 24-h variations in renal hemodynamics than does the method involving endogenous creatinine clearance as previously used in normal and obese rats (9,22). The present study documented circadian rhythmicity in GFR and RPF in chronically catheterized, unanesthetized, and freely moving rats, sampled repeatedly at 4-h intervals during the 24 h. Reproducible circadian changes were noted between animals and in the same animal assessed on consecutive days.…”
Section: Discussionsupporting
confidence: 60%
“…The circadian rhythm of plasma sodium is synchronous with the rhythms of circulating hormones, such as aldosterone (9,17,21), vasopressin, and oxytocin (31,34,51) and the renin-angiotensin system [i.e., angiotensin II (17,21,40), angiotensin-converting enzyme (44,47), and plasma renin activity (17,19,21,26)]. All of these rhythms are inverse to the rhythms of renal hemodynamics and excretion (18,29,38,39). Third, feeding and drinking patterns and the kinetics of gastrointestinal sodium absorption likely influence the plasma sodium rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that renal activity indices, like sympathetic activity, increase significantly during the day and decrease during the night; parasympathetic activity does the opposite [33,11,17]. Studies on renal activity diurnal variation have been carried out mainly on humans [13,3,31,5,15] and laboratory animals [32,1,43]. Few studies have been carried out on livestock.…”
Section: Diurnal Variability Of Renal Systemmentioning
confidence: 99%
“…The circadian rhythm of GFR in livestock is most likely affected by autonomic nervous system activity and also by circadian fluctuations of the following systems: the hypothalamus-hypophysis axis; vasoactive peptides; and, the renin-angiotensin-aldosterone complex, as studies on humans suggest [31,61]. Feeding time and diet (particularly the protein content in food) can modify renal activity, which results in hyperperfusion and then plasma hyperfiltration in renal glomeruli [58,32,52]. However, Muszczynski [35], in his studies on goats, did not observe an influence of feeding time on GFR diurnal variation.…”
Section: Effective Renal Blood and Plasma Flow And Glomerular Filtratmentioning
confidence: 99%
See 1 more Smart Citation